Increase of autophagy marker p62 in the placenta from pregnant women with preeclampsia - Ribeiro, Vanessa Rocha [UNESP]; Romao-Veiga, Mariana [UNESP]; Nunes, Priscila Rezeck [UNESP]; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP] (Elsevier B.V., 2022)
Preeclampsia (PE) is a multisystemic disorder characterized by abnormal placentation. Autophagy is a lysosomal degradation pathway that removes protein aggregates and damaged organelles, and it seems to be essential for cell survival during stress, hypoxia, and for implantation and development of the placenta. p62/SQSTM1 is an autophagy marker that not only binds proteins destined for elimination but is also constitutively degraded by this mechanism. Considering that the placenta plays an important role in the pathogenesis of PE, the present study aimed to evaluate the gene and protein expression of p62/ SQSTM1 in placentas from pregnant women with PE. Placental tissues from 20 women with PE classified into three groups according to gestational age, 27-31 weeks (n = 8); 32-36 weeks (n = 6); 37-39 weeks (n = 6), and 20 normotensives (NT) pregnant women were collected and employed for p62/SQSTM1 expression by quantitative polymerase chain reaction (qPCR), immunohistochemistry and enzyme linked immunosorbent assay (ELISA) techniques. p62/SQSTM1 mRNA levels were significantly lower, while protein expression was significantly higher in the placenta of pregnant women with PE than in NT pregnant women, and these results remained similar after separating the groups by gestational age. In conclusion, the results suggest that there is a reduction of autophagic activity in pregnant women with PE. Studies involving cross-talk between autophagy, inflammasomes, nuclear transcription factor (NF -KB) activation pathways, and aggregation of protein in the placenta from women with PE might help to better understand the pathogenesis of this important obstetric pathology. (c) 2022 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Autophagy; Homogenate; mRNA; Placenta; P62